2017
DOI: 10.4314/tjpr.v16i8.6
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of <i>Elephantopus scaber</i> L and <i>Sauropus androgynus</i> L merr extracts in modulating prolactin hormone and erythropoiesis in pregnant typhoid mice

Abstract: Purpose: To investigate the efficacy of Elephantopus scaber L. and Sauropus androgynus (L.) merr formulations in prolactin and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The study about E.scaber showed that this plant presence of minerals especially iron, calcium, magnesium, and zinc (Kabeer and Prathapan 2014) (Santhosh Kumar et al 2012). The other study revealed that the iron content on Elephantopus scaber were 45.4% (Djati et al 2017). One of bioactive compound of Curcuma zanthorrhiza was curcumin.…”
Section: Discussionmentioning
confidence: 90%
“…The study about E.scaber showed that this plant presence of minerals especially iron, calcium, magnesium, and zinc (Kabeer and Prathapan 2014) (Santhosh Kumar et al 2012). The other study revealed that the iron content on Elephantopus scaber were 45.4% (Djati et al 2017). One of bioactive compound of Curcuma zanthorrhiza was curcumin.…”
Section: Discussionmentioning
confidence: 90%
“…The liver and kidney were fixed in 10% formalin for 24 h. Then, the samples were processed by the standard procedure of paraffin embedding. The sections of about 5 μm were cut and stained with hematoxylin and eosin (H&E) [ 28 , 29 ]. The histological changes of kidney and liver were observed under BX51 light microscope with 10×40 magnification.…”
Section: Methodsmentioning
confidence: 99%
“…Their study helped to reveal the therapeutic potential of S. androgynus against mastitis. Djati et al [ 206 ] reported prolactin and erythrocyte inducing properties of S. androgynus leaves in pregnant mice induced with typhoid using Salmonella typhi . These studies prove the galactagogue property of S. androgynus .…”
Section: Pharmacology Of Sauropus Androgynusmentioning
confidence: 99%